Competence work culture and organizational commitment to the performance of Banten High Court employees Nurfitri - Nurfitri Nurfitri (Institute of Computer Science (IOCS), 2023)
Background: Modern justice is a mandate contained in the Blueprint for Judicial Reform 2010-2035, the implementation of which has started since the launch of e-court application in 2018. The Supreme Court has made various improvements to IT facilities and infrastructure and prepared reliable human resources that can support and accelerate the realization of modern justice. The contribution of this research is expected to provide information as a basis, consideration, support, and contribution of ideas to decision makers in improving employee performance at the Banten high court Objective: This study tries to see how much influence competence, work culture, and organizational commitment have on the performance of Banten High Court employees.Methodology: the method used in this study used a quantitative approach by collecting data through distributing questionnaires to measure employee perceptions with an interval scale of 1-10 to employees of Judges, civil servants and PPNPN. The sampling technique used simple random sampling and data processing using SmartPLS3.2.9. Limitation: The limitations in this study were only carried out on employees of Judges, Civil Servants and PPNPN and service users at the Banten High Court. The results of the study show that competence, work culture and organizational commitment have a positive and significant effect on the performance of employees in the Banten High Court.